Multi-band metamaterial antenna for terahertz applications - Shamsan, Zaid Ahmed; Isa Ashyap, Adel Yahya; Abbasi, Muhammad Inam; Kamarudin, ‪Muhammad Ramlee; Dahri, Muhammad Hashim; AlMuhanna, Khalid A.; Alorifi, Fawzi S. (Tech Science Press, 2023)
A multi-band metamaterial antenna is proposed to operate at the terahertz (THz) band for medical applications. The proposed structure is designed on a polyimide as a support layer, and its radiating elements are made of graphene. Initially, the design is started with a conventional shape showing a single operating frequency at 1.1 THz. To achieve a multi-band operating frequency, the conventional shape was replaced with the proposed metamaterial as a radiating patch that has properties not exist in nature. The multi-band frequencies are obtained without compromising the overall size of the design. The overall size is 600 × 600 × 25 μm3. The operating frequencies are 0.36, 0.49, 0.69, 0.87, and 1.04 THz. A full ground plane is used to behave as isolation between the design and the human body model. The proposed design is investigated on free space and on the human body model, showing excellent performance in both cases. The achieved gains for the following frequencies 0.36, 0.49, 0.69, 0.87, and 1.04 THz are 4.81, 6.5, 8.41, 6.02, and 7.96 dB, respectively, while the efficiencies are 83.91%, 96.28%, 90.80%, 91.71%, and 92.99%, respectively. The conventional design was modified to have a partial ground to show the benefit of using the full ground. The design is loaded on the human body model and its performance is affected. The efficiency and gain are 6.61 dB and 95.58.7% for the case of no human body model, and 4.26 dB and 40.30% for the case of using a human body model. Hence, the proposed metamaterial antenna will be useful for future medical applications in the THz band.